The Accuracy of Bedside Ultrasonography as a Diagnostic Tool for Fractures in the Ankle and Foot. (September 2014) - Atilla, Ozge Duman; Yesilaras, Murat; Kilic, Turgay Yilmaz; Tur, Feriyde Caliskan; Reisoglu, Ali; Sever, Mustafa; Aksay, Ersin; Moore, Chris
Abstract Objectives Ultrasonography (US) has been shown to be helpful in diagnosing fractures in the emergency department (ED) setting. The aim of this study was to determine the diagnostic accuracy of US for fractures in patients presenting to the ED with foot and/or ankle sprain and positive Ottawa foot and ankle rules. Methods This was a prospective study of consecutive patients aged 18 years and over were admitted to the ED with acute foot and/or ankle sprain and positive Ottawa foot and ankle rules. After the patients by were examined by bedside US, anteroposterior and lateral ankle radiographs were obtained, as well as anteroposterior and oblique foot radiographs. The films were evaluated by an orthopedic surgeon who was blinded to the US examination results. The orthopedic surgeon's evaluation was considered the criterion standard for diagnosing a fracture. Results A total of 246 patients were included in the study. In 76 (30.9%) of the patients, a total of 79 fractures were detected by radiography. Ten false‐negative and nine false‐positive results were obtained by US examination. Only one patient, whose US showed a fracture but whose radiographs were normal, had a fracture detected by computed tomography (CT). The sensitivity and specificity of US scanning in detecting fractures were 87.3% (95% confidence interval [CI] = 77.5% to 93.4%) and 96.4% (95% CI = 93.1% to 98.2%), respectively. Conclusions Ultrasound had good sensitivity and specificity for diagnosing fifth metatarsal, lateral, and medial malleolus fractures in the patients with foot and/or ankle sprain. However, sensitivity and specificity of US for navicular fractures were low.